KRITIK KEPADA WAKIL RAKYAT DALAM LAGU IWAN FALS - Alexander Bala (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2020)
The criticism in Iwan Fals' song aims to remind the people's representatives in parliament to sincerely and wholeheartedly fight for the welfare of the community. By avoiding conspiracy through corruption, collusion, and nepotism against community development funds. Thus, a people's representative must continue to act as a channel for people's aspirations through various policies regarding the people in parliament.